Towards an Indigenous Museology: Native American and First Nations Representation and Voice in North American Museums - Ryker-Crawford, Jessie V. (2017)
Thesis (Ph.D.)--University of Washington, 2017 The museum field has had a definite impact on the identity of Native American and First Nations peoples, perhaps more than on any other cultural group. Yet the dynamics and historical relations between museums and these populations have been contentious at best. This dissertation examines museums and their history through an Indigenous lens. It explores how the museum field has changed and enriched its philosophical and educational missions due to the modification of collections, curatorial, and conservation practices brought about by Native American and First Nations peoples. It addresses how this has transformed museums across the globe and has impacted the field of museology through the delivery of a more inclusive museum studies curriculum.